(3eOi edGAeI GdLRGAGJ GdLfGFjI GdGbJUGOjI ai Xd GdSjGSI GdLfGFjI GdeYGUQI (B: s (3OQGSI JMdjdjI JCUjdjI ebGQfI (B/ s - (3eMeO YHOGdYRjR eMeO GdSjO GdTQjas; (3eCehf SdGeIs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2005)
(3jCJi ehVhYeOi edGAeI GdLRGAGJ GdLfGFjI GdGbJUGOjI ai Xd GdSjGSI GdLfGFjI GdeYGUQI ai GWGQ GdadSaI GdbGfhfjI hGdabgjI GdMOjKI (B: (3hGdGJLGg GdMOjK ddabg GdLfGFi GdeYGUQ (B: (3dehGLgI GdJLQje GdGbJUGOi GdPi jJWhQ ef Gf dGNQ ai eLJeYfG GdeYGUQ (B: (3hcPdc dJMbjb GdMeGjI GdLfGFjI ddSjGSI GdGbJUGOjI ai GdHdGO hGbJUGOgG Gdbhei GdPi gh YUH GdMjGI ajgG hjCJi gPG GdehVhY ai bSejf cHjQjf (B: (3jSHbgeG HGH JegjOi fJfGhd ajg GdJWhQ GdJGQjNi deaghe GdLRGA GdLfGFi ai eLGd GdJLQje GdGbJUGOi heG WQC Ydjg efP GdYUhQ GdbOjeI hMJi GdYUQ GdMOjK ai GdbGfhf GdeUQi hGdebGQf ai GdYOjO ef GdOhd GdZQHjI hGdGaQjbjI hGdGSjhjI hGdYQHjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2005s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B526-566s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLRGAGJ GdLfGFjI GdGbJUGOjIs; (3GdSjGSI GdLfGFjI GdeYGUQIs; (3GdadSaI GdbGfhfjIs; (3GdYbhHIs; (3GdJgQH GdVQjHis; (3GdeUGOQIs; (3GdJgQjH GdLeQcis; (3GdLQGFe GdGbJUGOjIs; (3GdJRhjQ GdVQjHis; (3eCehQi GdVHWs; (3GdJUGdMs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs